Effects of system control strategies on startup characteristics of R290 room air conditioners. (25th May 2020) - Wu, Jianhua; Li, Jinbo; Wang, Che; Du, Yanjun; Chen, Rui
Highlights: Startup characteristics under various system control strategies were studied. Warm startup promotes the formation of liquid R290 before the expansion valve. Larger initial expansion valve opening avoided the vacuum. Bypass could also provide more refrigerant to low pressure side. Abstract: The operation of R290 air conditioners at cold ambient temperatures can lead to sub-atmospheric suction pressures, risking the safety and reliability of such air conditioners. In this study, the effects of several system control strategies on the startup characteristics were investigated, with the goal of avoiding vacuums in air conditioners. The variations in the degrees of superheating and the changes in the flow patterns at key points were analyzed. The refrigerant migrations and pressure variations indicated that owing to the higher initial temperatures in a warm startup, the heat inertia of the compressor and indoor heat exchanger contributed to the formation of liquid refrigerant at the expansion valve inlet, as well as an increase in the suction pressure. Moreover, using larger initial expansion valve openings or a bypass tube between discharge and suction could increase the minimum suction pressures, by providing more R290 refrigerant to the low-pressure side at the beginning of startup.